Joy at birth an interpretive, hermeneutic, phenomenological inquiry - Crowther, Susan (Routledge Research in Nursing and Midwifery Ser, 2019)
To be at the birth of a baby is special, yet there is an increasing secularisation and reliance on technology in contemporary maternity care, particularly in the western context. Through exploration of experiences at birth this book explores joy at birth, which is often ignored and overlooked beyond the activities that help to ensure survival. This book draws on a collection of stories of birth from mothers, birth partners, obstetricians and midwives, that demonstrate joy at birth across professional groups and in different types of births and locations with or without technological interventions. Each chapter introduces stories of joy that highlight embodied, spatial and relational meanings. Employing the Heideggerian notion of a human being, it sketches out an ontological focus that draws our gaze to the everyday taken-for-granted ways of being at birth. Based on phenomenological experiential data and rigorous interpretive analysis underpinned by seminal philosophical writings, this book calls for readers to attend to the wholeness of birth in all situations and at all births in ways not attempted before. It will be of great interest to midwives, and those working in and studying maternity, obstetrics and neonatology, as well as social and medical anthropology, sociology, cultural, organisational and clinical psychology and spirituality